2016
DOI: 10.1515/sspjce-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Determination of VOCs in the Indoor Air of a New and a Renovated Apartment

Abstract: This study deals with the occurrence of volatile organic compounds (VOCs) in the indoor environment of a new and a renovated apartment. Qualitative determination of VOCs was carried out with a gas chromatograph with surface acoustic wave detector (GC/SAW). Concentrations of total volatile organic compounds (TVOC) were determined by a photoionization detector with UV lamp. Simultaneously, temperature and relative humidity were monitored with a data logger. The aim of this study was to determine of TVOC concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…[65][66][67][68][69] Carvone, which was primarily observed in non-denuded indoor chromatograms, is an oxidized terpene that, like other terpenes, emits as a primary product from wood, paints, and scented indoor items, but also originates from gas-phase oxidation of limonene. 132,133 Although the limonene-ozone pathway might contribute partly to carvone concentrations, we do not expect significant carvone production through this mechanism based on low observed limonene concentrations.…”
Section: Enhanced Emission Of Indoor Speciesmentioning
confidence: 80%
See 1 more Smart Citation
“…[65][66][67][68][69] Carvone, which was primarily observed in non-denuded indoor chromatograms, is an oxidized terpene that, like other terpenes, emits as a primary product from wood, paints, and scented indoor items, but also originates from gas-phase oxidation of limonene. 132,133 Although the limonene-ozone pathway might contribute partly to carvone concentrations, we do not expect significant carvone production through this mechanism based on low observed limonene concentrations.…”
Section: Enhanced Emission Of Indoor Speciesmentioning
confidence: 80%
“…Though relative factor loadings may vary between denuded and non‐denuded measurements for a given compound, Factors 1‐D and 2‐D generally have contributions from personal care product ingredients (eg, isopropyl myristate and DEET), perfumes (eg, hedione and α‐cedrene), and plasticizers (eg, diethyl phthalate, dibutyl phthalate, and dimethyl phthalate loading into both indoor factors 1 and 2) . Carvone, which was primarily observed in non‐denuded indoor chromatograms, is an oxidized terpene that, like other terpenes, emits as a primary product from wood, paints, and scented indoor items, but also originates from gas‐phase oxidation of limonene . Although the limonene‐ozone pathway might contribute partly to carvone concentrations, we do not expect significant carvone production through this mechanism based on low observed limonene concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…There are a limited number of studies investigating the botanical biofiltration of multiple VOCs simultaneously, however it is likely that there may be interactions that would influence removal efficiency. Although this work evaluated the removal of different VOCs individually, it has been shown that a complex mixture of VOCs exist within most indoor environments (Meciarova and Vilcekova, 2016). Potted-plant experiments that have assessed the simultaneous removal of multiple VOCs have found that this may improve or hinder the rate of microbial degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile organic compounds (VOCs) are an important class of air pollutants present in many indoor environments (Cakmak et al, 2014;Wang et al, 2013a;Wolkoff, 2013), where their concentration is often much higher than in the corresponding outdoor environment (United States Environmental Protection Agency, 2017). Several hundred VOCs have been reported in the indoor environment (Meciarova and Vilcekova, 2016) and exposure to certain VOCs has been associated with a broad range of symptoms including asthma and allergic disorders (Garrett et al, 1999;Krzyzanowski et al, 1990;Norbäck et al, 1995;Rumchev et al, 2002;Venn et al, 2003), while some VOCs, such as benzene, can have carcinogenic effects (Mehlman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While many experiments have assessed the potential for the bioremediation of single VOCs independently, hundreds of VOCs may be present simultaneously in a typical indoor environment (Meciarova and Vilcekova, 2016). Simultaneous biodegradation of multiple VOCs provides the opportunity for substrate interactions to occur.…”
Section: Potting Substrate Materials and Substrate Microorganism Effectsmentioning
confidence: 99%